The Effect of Cash Turnover and Inventory Turnover on Return on Assets (ROA) - Annisa Intan Nuraini (Almana : Jurnal Manajemen dan Bisnis, 2021)
Profitability has an important role in the company. The profitability ratio that is often used is Return On Assets (ROA). The use of funds and the company must be effective, to be able to determine how much working capital the company has, it can be seen from its cash turnover and inventory turnover. The objective of this research is to analyze the effect of Cash Turnover and Inventory Turnover on Return On assets. This research used a sample of retail trade subsector companies in the Indonesia Stock Exchange in 2015-2020. Based on the purposive sampling method, the total sample of this research was 36 financial statements. The hypothesis testing in this research was done using multiple regression techniques at a significance level of 5%. The research results indicate that simultaneously Cash Turnover and Inventory Turnover affect Return On Assets. This is evidenced by the F-observed value of 267.341 which is greater than the Ftable of 4.14 and a significance value of 0.000 which means it is smaller than 0.05. In addition, the coefficient of determination (R2) of 0.938, indicates that each Return On Asset is influenced by Cash Turnover and Inventory Turnover by 93.8% while the remaining 6.2% is influenced by other variables.